EFFORTS TO REDUCE THE KNEE JOINT PAIN COMPLAINTS IN ELDERLY ELDERLY POSYANDU PROSPER - Handono, Sri; Richard, Selvia David (Jurnal Penelitian STIKES Kediri, 2013)
Pain in the elderly, one of which resulted because of the aging process in the musculoskeletal system. The objective is study of the behavior of older adults in treatment of knee joint pain in the elderly Integrated Health Sejahtera GBI Setia Bakti Kediri. Design was descriptive, with a sample of 50 elderly, acidental sampling technique. Research variables the behavior of older adults in treatment of knee joint pain. Data questionnaires were analyzed by frequency distribution. Based on the analysis results showed most respondents have a behavior management of knee pain with good medikamentosa is 22 respondents (44.0%), more than 50% with posture correction is 32 respondents (64.0%), more than 50% with diet is 30 respondents (60.0%), more than 50% with either conservative therapy is 29 respondents (58.0%). Â The conclusion of this study is the behavior of older adults in treatment of knee joint pain with medical, posture correction, diet, conservative therapy has been well.